A method of fine size measurement for telecentricity-based error compensation. (2nd July 2021) - Li, Wenjie; Wang, Haiwang; Tang, Rongjiang; Jiang, Zhansi; Li, Tengfei; Huang, Meikuan; Gao, Xingyu
Abstract: Focusing on the stable magnification, near zero distortion, and wide field of depth (DoF), the telecentric optical system is well suited for size measurements with a large range of working distances. However, suffering from the telecentricity-based error (TBE), the size measurement is connected with the working distances and imaging position of the image sensor, even within the DoF. Therefore, a model of TBE compensation is established, inspired by the radial distortion model in the camera calibration. With the correction of radial distortion coefficients for different working distances, the TBE is evidently improved. The feasibility of the proposed method is verified both in the theory and experiment. Our results show that the uncertainty of size measurement at different working distances of the DoF is improved obviously after the TBE compensation, which is attractive for fine size measurements in industry.